Understanding Learning Outcomes: The Predictive Roles of Academic Resilience and Student Engagement - Armiati Armiati; Windi Rahmawati; Dessi Susanti (Jurnal Ecogen, 2026)
This study examines the extent to which academic resilience and student engagement predict students’ learning outcomes in a vocational education context. Despite increasing attention to these factors, prior research has largely examined them separately and has focused more on general or higher education settings, leaving their combined role in vocational secondary education, particularly in developing countries, underexplored. Addressing this gap, this study adopts a quantitative approach with an explanatory design and was conducted at SMKN 1 Painan, West Sumatra, Indonesia. A total of 190 eleventh-grade students were selected from a population of 359 using proportional random sampling. Data were collected through structured questionnaires and school records and analyzed using multiple linear regression. The results indicate that academic resilience and student engagement significantly predict students’ learning outcomes, both individually and simultaneously, explaining 37.9% of the variance. This study offers a distinct contribution by examining persistence in facing academic challenges and active participation in learning within a single analytical framework in a vocational education context. These findings imply that strengthening students’ persistence and promoting active involvement through interactive and practice-oriented learning strategies are essential for improving academic performance.